Level of Smartphone Addiction, Sleep Quality and Affecting Factors in University Students: A Cross-Sectional Study - Çelebi, Evrim (My University, 2023)
Objective: This research was conducted to determine the smartphone addiction levels, sleep quality and affecting factors of mid- wifery students studying at a state university.Material and Methods: The population of the cross-sectional study consisted of 296 students at- tending the midwifery department of a state university in the spring semester of the 2019-2020 academic year. Purposive sampling method was used in this study. All of the students in the population were in- cluded in the study and the study was completed with 247 students. The response rate was 83.4%. Data collection tools were as follows: the per- sonal information form, Smartphone Addiction Scale-Short Form (SAS-SF) and tools Pittsburgh Sleep Quality Index (PSQI) were used. Results: Their mean age was 20.91±1.42 years. The mean scores the students obtained from the overall SAS-SF and PSQI were 31.57±11.27 (minimum: 10, maximum: 60) and 7.64±2.68 (minimum: 3, maximum: 17) respectively. While the participating students’ smartphone addiction was at a moderate level, their sleep quality was at a poor level. There was a positive and significant correlation between Smartphone Addic- tion and Sleep Quality. Conclusion: Trainings and interventional stud- ies can be conducted to reduce the time spent using smartphones and improve sleep quality among university students.
Keywords: Smartphone; addiction; sleep quality; midwifery